Relationships between Teacher Qualification, Teacher Behaviour/Practices and Teacher Skills/Expertise: Teacher Quality, Practices and Skills - Sie, Charles Kwabena; Chonga , Kipo (International Journal of Educational Innovation and Research, 2025)
The central aim of this research was to identity the relationships between the perceived teacher quality constructs of elementary school mathematics instructors. The research employed a purposive sampling approach to select 50 mathematics teachers in the Bole District of the Savannah Region in Ghana to participate in the study. Specifically, 50 mathematics teachers were given questionnaires on teacher skills/expertise, teacher behaviour/practices and teacher qualification to establish the relationships between these variables. The results from the research with a correlation coefficient, r = 0.443 and a P-value of 0.001, revealed that teacher skills/expertise was statistically significantly correlated with Teacher behaviour/practices. The results from the mathematics teachers did not show significant relationships between teacher qualification and the other parameters of the study. This study showed that the interconnectedness between teacher skills/expertise and teacher behaviour/practices is a cornerstone of effective education. The implication of this study is that teachers’ academic qualifications do not always guarantee comprehensive knowledge of teaching.  A comprehensive knowledge of teaching requires the acquisition of the three competencies (professional values and attitudes, professional knowledge and professional practice) as contained in the National Teachers standards. This study has impact on the training and organization of professional development programs for mathematics teachers in Ghana and other countries with similar contexts. The researchers recommend that teacher training institutions should focus on the training of teachers to acquire the competencies necessary for effective teaching and learning. Teacher professional development opportunities should be made available to teachers as a way of developing their professional values and attitudes, professional knowledge and professional practices that are required to teach effectively.